"Religious and Educational Reforms of Mufti Mahmood as Chief Minister (N.W.F.P) " - Abdul Hakeem Akbari. (الإيضاح, 2008)
"Late Mufti Mahmood was a person with comprehensive leadership qualities not only confined to politics but having a broader vision of Education, Islamic Jurisprudence, Constitution and Parliamentary affairs, He was not only popular in Pakistan but also the Ulama of India, Bangladesh, Egypt and even Saudi Arabia quenched thirst of religious guidance from him.